Statistically Convergent Sequences in Neutrosophic Metric Spaces - Ali, Usman; Umar Ishtiaq; Khaleel Ahmad; Jahanzaib (Scientific Inquiry and Review, 2022)
In this study, the introduction of statistical convergence and statistical Cauchy sequences with respect to neutrosophic metric spaces is motivated by the notion of statistical convergence in fuzzy metric spaces. We offer useful characterizations for statistically convergent and statistically Cauchy sequences.